Review on Production of Single-Cell Protein from Food Wastes - Nura Abdullahi; Munir Abba Dandago; Alkasim Kabiru Yunusa (Turkish Journal of Agriculture: Food Science and Technology)
The roles of protein in bodybuilding and the regulation of biological processes are important in sustaining life. A large amount of protein is required by both humans and animals and this cannot be supplied by only conventional sources. This is because of the rapid increase in world population. The present sources of protein will not meet global protein demand in years to come. Scientists explore the production of single-cell protein (SCP), as an alternative source of protein, through the utilization of wastes and low-value materials. SCP can supply high-quality protein containing both essential and non-essential amino acids that can be utilized by humans and animals. Protein from microbial biomass is cheaper than animal proteins because the substrates used in the production are generally cheaper and more readily available. Moreover, the production process does not require arable land and the entire process can be completed within a short time. This article reviewed the process of SCP production. Different raw materials used in the production and variations in growth media preparation methods were discussed. Various sources of fermentation microorganisms and their potential substrate were reviewed. Growth media enrichment using different carbon, nitrogen, and mineral sources was also discussed.